Effort to Improve the Quality of Education with A Social and Cultural Approach in Bah Butong Village II - Mesiono Mesiono; Syafri Fadillah Marpaung; Muhammad Al Fatih; Fazli Abdillah; FilmaMuhazri Sembiring (Edumaspul: Jurnal Pendidikan, 2022)
Community Service (Pema) is a tangible manifestation of the duties of lecturers and students in implementing the Tri Dharma of Higher Education, namely the aspect of service. Through community service activities in Bah Butong II village, there is a synergy between universities and the community as a form of participation in the Bah Butong II village community. The purpose of this service is to provide understanding to the local community about the importance of education and preserving the cultures that exist in the village of Bah Butong in order to assist the village government in educating the community and the children of the nation's successors. The service is carried out through the following activities: Education, teaching, socialization, mutual cooperation and enlivening the independence day. The results of this community service provide enthusiasm and increase public understanding, especially teachers and parents about education, social, culture in order to give birth to the next generation who have spiritual and intellectual understanding.